The Supreme Court: On Carrying Concealed Weapons, in State Journal, Apr. 12, 1878 - (:unkn) unknown (My University, 1878)
Regulated conceal carrying where people may be assembled for educational, literary, or social purposes, or to any election precinct on any election day, or into any court room during the sitting of court, or into any other publica assemblage of persons met for other than militia drill or meetings called under the militia laws of the State, having concealed about his person any kind of fire arms, bowie knife, dirk, dagger, slung shot, or other deadly weapon shall be guilty of a misdemeanor.
Keywords: CARRY - CERTAIN PUBLIC PLACES; CARRY - CONCEALED